Review: Insects and former foodstuffs for upgrading food waste biomasses/streams to feed ingredients for farm animals. (29th January 2019) - Pinotti, L.; Giromini, C.; Ottoboni, M.; Tretola, M.; Marchis, D.
Abstract : The increasing global need to find alternative protein/energy sources has triggered research in the field of non-conventional feed ingredients, with insects and former foodstuffs being the most promising. Insects contain high level of protein and fat, whereas former foodstuffs contain high energy in the form of carbohydrates and fats; therefore, both should be considered as promising alternative feed ingredients for livestock production. In addition to the nutritional value, they also represent a way by which food waste biomasses/streams can be upgraded to valuable feed ingredients. This review outlines the main nutritional and safety issues of insects and former foodstuffs, and also considers the legal framework involved. The importance of the type of insect metamorphosis and tailored substrates that could lead to the production of a premium feed is also described. This is also the first time that a review discusses the nutritional quality of former foodstuffs. Energy and the main nutrient content of former foodstuff are compared with the composition of common cereals as the principal energy sources in animal feed. For both ingredients a critical review of the safety issues is provided. Based on the current data available, both insects and former foodstuffs have an excellent potential use as alternative feed ingredients for livestock production. When produced in line with the criteria set by major feed/food authorities, they are characterized by high quality and safety standards. This makes them comparable to other feed materials and ingredients currently available on the market, although their full nutritional, functional, safety and sustainability evaluation cannot be considered complete.